2016
DOI: 10.1155/2016/6762343
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Zinc Signaling in the Immune System

Abstract: Zinc (Zn) is an essential micronutrient for basic cell activities such as cell growth, differentiation, and survival. Zn deficiency depresses both innate and adaptive immune responses. However, the precise physiological mechanisms of the Zn-mediated regulation of the immune system have been largely unclear. Zn homeostasis is tightly controlled by the coordinated activity of Zn transporters and metallothioneins, which regulate the transport, distribution, and storage of Zn. There is growing evidence that Zn beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
199
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 201 publications
(243 reference statements)
0
199
0
9
Order By: Relevance
“…is state in the body also contributes to atrophy of the thymus as well as reducing the number of mature T lymphocytes [77]. An appropriate level of zinc is important for the activation of T cells and their proper functioning [78]. In animal studies, zinc deficiency has been shown to reduce the production of IL-2, a factor that influences the growth of mainly cytotoxic T lymphocytes [78].…”
Section: Zinc Zinc Is a Food Component Classed As A Micronutrientmentioning
confidence: 99%
See 1 more Smart Citation
“…is state in the body also contributes to atrophy of the thymus as well as reducing the number of mature T lymphocytes [77]. An appropriate level of zinc is important for the activation of T cells and their proper functioning [78]. In animal studies, zinc deficiency has been shown to reduce the production of IL-2, a factor that influences the growth of mainly cytotoxic T lymphocytes [78].…”
Section: Zinc Zinc Is a Food Component Classed As A Micronutrientmentioning
confidence: 99%
“…An appropriate level of zinc is important for the activation of T cells and their proper functioning [78]. In animal studies, zinc deficiency has been shown to reduce the production of IL-2, a factor that influences the growth of mainly cytotoxic T lymphocytes [78]. A deficiency may cause apoptosis of mature B lymphocytes and reduce the number of immature B lymphocytes.…”
Section: Zinc Zinc Is a Food Component Classed As A Micronutrientmentioning
confidence: 99%
“…Appropriate levels of zinc are required for the proper functioning of the immune system while excessive zinc intake has shown negative effects on it (Wessels et al 2017). In innate immunity, zinc keeps the epithelial membrane of natural barrier structure and function (Hojyo and Fukada 2016). Acute zinc deficiency causes a decrease in innate immunity (Gruber and Rink 2013;Rink and Gabriel 2000), while chronic deficiency increases inflammation (Maares and Haase 2016;Barnett et al 2016).…”
Section: Trace Elementsmentioning
confidence: 99%
“…At present it is known 24 various Zn transporters, of which 14 mediate inward (into cytoplasm) Zn transport (ZIP family) and 10 mediate outward (from cytoplasm into extracellular space or into intracellular organelles) Zn transport (ZnT family). [23] In T cell activation dendritic cells or other antigen presenting cells (APC) form a contact with T cell, forming a kind of an immunologic synapse. In this contact peptide containing class I and/or class II MHC molecule (pMHC) on the surface of APC contacts cognate T cell receptor (TCR).…”
Section: Role Of Zinc In T Cell Activationmentioning
confidence: 99%
“…Zinc concentration increases particularly in the subsynaptic region of T cell (a kind of zinc wave). [23][24][25] Up to date experiments concerning the effects of zinc on immune activation has been done with Zinc salts (free Zn 2+ ion). No one studies done with complexated particle bound zinc cannot be found in literature.…”
Section: Role Of Zinc In T Cell Activationmentioning
confidence: 99%